2017
DOI: 10.1039/c7ta05483a
|View full text |Cite
|
Sign up to set email alerts
|

An oxidized magnetic Au single atom on doped TiO2(110) becomes a high performance CO oxidation catalyst due to the charge effect

Abstract: Catalysis using gold nanoparticles supported on oxides has been under extensive investigation for many important application processes. However, how to tune the charge state of a given Au species to perform a specific chemical reaction, e.g. CO oxidation, remains elusive. Here, using first-principles calculations, we show clearly that an intrinsically inert Au anion deposited on oxygen-deficient TiO 2 (110) (Au@TiO 2 (110)) can be tuned and optimized into a highly effective single atom catalyst (SAC), due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 61 publications
1
37
0
Order By: Relevance
“…However, most experimental evidence points toward al ower activity of SAs compared to metal clusters. [58] In contrast, as tudy of B-and N-doped carbon supports indicated that anionic Au species formed in the presence of boron were more active because CO was less strongly adsorbed than it would otherwise be on Au cations. [51] Au 1 /CeO 2 was later shown to be stable for the preferential oxidation of CO in H 2 -rich streams.…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…However, most experimental evidence points toward al ower activity of SAs compared to metal clusters. [58] In contrast, as tudy of B-and N-doped carbon supports indicated that anionic Au species formed in the presence of boron were more active because CO was less strongly adsorbed than it would otherwise be on Au cations. [51] Au 1 /CeO 2 was later shown to be stable for the preferential oxidation of CO in H 2 -rich streams.…”
Section: Methodsmentioning
confidence: 95%
“…As ac onsequence of the known activity in this reaction, Au-based systems have attracted significant attention. [58,62,92] Maximizing the degree of oxidation by doping with as econd transition metal was predicted to yield the highest activity for Au 1 /TiO 2 systems. [87][88][89][90] On the other hand, Qiao et al highlighted ap otential advantage of SAs for demonstrating increased resistance to sintering of Au 1 /FeO x compared to larger Au nanostructures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations